The UK National Quantum Technology Hub in Sensors and Metrology - Bongs, K.; Boyer, V.; Cruise, M.A.; Freise, A.; Holynski, M.; Hughes, J.B.; Kaushik, A.; Lien, Y.-H.; Niggebaum, A.; Perea-Ortiz, M.; Petrov, P.; Plant, S.; et al. (SPIE, 2016)
The UK National Quantum Technology Hub in Sensors and Metrology is one of four flagship initiatives in the UK National of Quantum Technology Program. As part of a 20-year vision it translates laboratory demonstrations to deployable practical devices, with game-changing miniaturized components and prototypes that transform the state-of-the-art for quantum sensors and metrology. It brings together experts from the Universities of Birmingham, Glasgow, Nottingham, Southampton, Strathclyde and Sussex, NPL and currently links to over 15 leading international academic institutions and over 70 companies to build the supply chains and routes to market needed to bring 10–1000x improvements in sensing applications. It seeks, and is open to, additional partners for new application development and creates a point of easy open access to the facilities and supply chains that it stimulates or nurtures.